MNEMONICS AND DENUNCIATION IN MAPUCHE ECOPOETRY: ELICURA CHIHUAILAF, LEONEL LIENLAF AND LORENZO AILLAPÁN - Fierro-Concha, Marina (2026)
This article analyzes, from an ecocritical perspective, the ecological poetry of Leonel Lienlaf, Lorenzo Aillapan and Elicura Chihuailaf. Ecopoetry should be understood as the intellectual and aesthetic link to achieve an ecological orientation, therefore, a selection of poems was prepared extracted from the collections of De sueños azules y contrasueños (1995), Üñümche: Hombre pájaro (2003), Sueños de luna azul (2008), Se ha despertado el ave de mi corazón (2011) y Üñüm Püllü. Espíritu Pájaro (2019), this with the purpose of emphasizing the importance of the man-nature relationship from the perspective of memory and denunciation. The symbolic dimension used by the authors is directly connected to the ethnocultural ambit of the Mapuche people; a space that, although it is not the main object of analysis, is nevertheless essential whitin its considerations. The article seeks to highlight man's dialogue with nature and highlight the concepts of mnemonic and denunciation, which are used by Lienlaf, Aillapan and Chihuailaf to express their concern for environmental reality.